Paradigmatic Transition: Social Entrepreneurship as a Catalyst for Enhancing the Competitiveness and Sustainability of SMEs in the Digital Business Context - Prety Diawati; Sutrisno; Dewa Oka Suparwata (Politeknik Ganesha Medan, 2024)
In recent decades, there has been a paradigm shift in how we perceive business. It is no longer solely about profit-making but also about considering the social and environmental impacts of business activities. This research aims to delve deeper into how social entrepreneurship can be implemented in the context of digital business to support the competitiveness and sustainability of SMEs. The research method employed is a qualitative literature review drawing data from Google Scholar within the timeframe of 2020-2024. A qualitative approach is used to understand and analyze various perspectives, theories, research findings, and concepts relevant to the research topic. The study findings indicate that the paradigmatic transition occurring in the business world today reflects the rapid and complex global changes. The evolving digital era has triggered a shift from traditional business paradigms towards more inclusive and sustainable approaches. Social entrepreneurship emerges as a significant catalyst in strengthening the competitiveness and sustainability of micro, small, and medium enterprises (SMEs) in the digital business environment. It is important to understand that social entrepreneurship is not just about seeking financial profit alone but also about advocating for social and environmental change.